Structural Inequality and COVID-19 Mortality in Chicago: An Ecological Analysis. - Patterson, Evelyn J.; Johnson, Lallen T. (Journal of Racial & Ethnic Health Disparities, 2023)
Background: Prior studies establish that Black neighborhoods and older persons experience higher rates of COVID-19 death than white neighborhoods and younger persons. However, such works point to the effect of age on COVID-19 mortality and the racial and ethnic inequalities present in COVID-19 deaths as independent vectors of inequality, neglecting to consider the multiplicative impact of structural conditions. Methods: Using weekly ZIP code counts of deaths from March 2020 through July 2021 from the Chicago Department of Public Health (n = 4168) and measures of structural characteristics derived from the 5-year estimates of the 2019 American Community Survey, the current study examined how place, racial composition, and the age structure of communities act in tandem to shape the number of deaths due to COVID-19. We used STATA to estimate negative binomial models predictive of COVID-19 mortality. Results: Findings from our statistical analysis revealed that in predominately Black neighborhoods, racial composition amplified the association of age structure (65 +) on COVID-19 mortality by 40%. Neighborhoods that were not predominately black did not show this multiplicative risk of death. Our findings underscore that the elevated risk of death in in older Black communities is attributed to historic and contemporary structural inequality. Conclusions: Although society typically frames pandemics as natural disasters, doing such undermines dimensions of marginalization that amplify vulnerability among select populations. To begin eliminating such inequalities, the USA must deal with the entrenched limitations of institutions that render unequal attention and care to sectors of its population.